Possíveis significações na clínica psicanalítica a partir do estudo dos mecanismos de recalque e recusa e da dissociação do ego - Alves, Ester (2007)
The propose of this dissertation is joint the listening and transfering of a patient in analyses and the psychoanalytic theory, specially, concerning the concepts of repression, denial and ego's dissociation. It shows a clinic case that promove questions, in proportions of reveals to the analyst subject that indicate the presence of the repression and denial concomitant, and, therefore, points to some diagnostics, specifically, to perversion, neurosis e narcisic neurosis. From the worked containt, come to light this signification's possibilitys to the observables in the clinic, beyond therapeutics alternatives